Socialization and Practice of Processing Organic Waste into Eco-Enzyme at Sungai Nanam - Elara Resigia; Aswaldi Anwar; Indra Dwipa; Irawati Irawati; Armansyah Armansyah; Sanna Paija Hasibuan; Nilla Kristina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The village of Sungai Nanam, Lembah Gumanti, is an area in Solok Regency, West Sumatra, that produces significant organic waste from horticultural agriculture. If not managed properly, this waste can cause environmental and aesthetic issues. However, this waste can be converted into an eco-enzyme. An eco-enzyme is a liquid enzyme produced by fermenting organic waste. Eco-enzyme has many benefits, including being used as a liquid organic fertilizer, cleaner, and pest repellent. This community service aims to educate and train the community, especially the women farmers group, named Kelompok Wanita Tani (KWT) Rimbo Data Sejahtera, on converting organic waste into eco-enzymes. The program used three methods: socialization, demonstration, and mentoring. It has been proven to be an effective way to educate and train the community, particularly KWT Rimbo Data Sejahtera, on proper waste management. This program is a perfect fit for their needs and is very useful in reducing the impact of pollution.